Application of stimuli-responsive hydrogel in brain disease treatment - Xie, Bingqing; Xie, Huangfan (Frontiers in Bioengineering and Biotechnology, 2024)
Treating brain diseases presents significant challenges due to neuronal degeneration, inflammation, and the intricate nature of the brain. Stimuli-responsive hydrogels, designed to closely resemble the brain's extracellular matrix, have emerged as promising candidates for controlled drug delivery and tissue engineering. These hydrogels have the unique ability to encapsulate therapeutic agents and release them in a controlled manner when triggered by environmental stimuli. This property makes them particularly suitable for delivering drugs precisely to targeted areas of the brain, while minimizing collateral damage to healthy tissue. Their preclinical success in treating various brain diseases in animal studies underscores their translational potential for human brain disease treatment. However, a deeper understanding of their long-term behavior, biodistribution, and biocompatibility within the brain remains crucial. Furthermore, exploring novel hydrogel systems and therapeutic combinations is paramount for advancing towards more effective treatments. This review summarizes the latest advancements in this field over the past five years, specifically highlighting preclinical progress with novel stimuli-responsive hydrogels for treating brain diseases.